A não associação entre adesão medicamentosa e o controle glicêmico em participantes diabéticos do ELSA-Brasil - Moraes, Helaine Aparecida Bonatto de (2017)
Introduction: Drug adherence has been identified as a relevant problem for clinical practice, since it has been attributed to the failure of metabolic control in diabetics. Objective: To investigate the adherence to medication and its relation with the glycemic control of diabetics of the Longitudinal Study of Adult Health (ELSA-Brazil). Method: Sectional study with ELSA-Brazil baseline data, 2008-2010. Sample with 1242 self-reported diabetics, with data obtained through interview and biochemical tests. The variables consisted of glycated hemoglobin as an outcome, adherence to the drug as exposure and socioeconomic, demographic covariables, as to life, food and nutritional habits, and type of medication. For the analysis, ANOVA or KruskalWallis and multinomial logistic regression were used, with glycemic control as standard and p<5%. Results: Overweight and obesity were present in 82.8%, 56.2% consumed alcoholic beverages, 96.6% were inactive, almost one third with a diet of over 3,000 calories, 54.2% with glycated hemoglobin > 6.5%, and almost 70% had fasting blood glucose ≥ 126 mg / dl and only 40% had high drug compliance. Increased chance of elevated glycated hemoglobin in males (OR: 1.393; CI: 1.051- 1.846); race / color black (OR: 1,739; CI: 1,219-2,481) and brown (OR: 1,569; CI: 1,137-2,165); mean occupation level (OR: 1.627; CI: 1.024-2.584); not having a health plan (OR: 1.467; CI: 1.096 - 1.965); use of insulin alone (OR: 7.341; CI: 3.556- 15.154) or associated with oral hypoglycemic (OR: 7.579; CI: 3.956-14.520); altered WHR (OR: 1.867; CI: 1.191-2.928); smoking habit (OR: 1.730; CI: 1.093-2.738) and poor / very poor health self-assessment (OR: 2.374; CI: 1.167-4.827). Conclusion: The variables associated with metabolic control were related to the social determinants of health, lifestyle and especially those related to health condition such as insulin use and health self-assessment.